Improving Thermostability and Catalytic Activity of Glycosyltransferase From Panax ginseng by Semi-Rational Design for Rebaudioside D Synthesis - Chen, Meiqi; Song, Fangwei; Qin, Yuxi; Han, Shuangyan; Rao, Yijian; Liang, Shuli; Lin, Ying (Frontiers in Bioengineering and Biotechnology, 2022)
As a natural sweetener and sucrose substitute, the biosynthesis and application of steviol glycosides, containing the component rebaudioside D, have been attracted worldwide attention. Here, a glycosyltransferase PgUGT from Panax ginseng was firstly reported for the biosynthesis of rebaudioside D. With the three-dimensional structures built by homology modelling and deep-learning based modelling, PgUGT was semi-rational designed by FireProt. After detecting 16 site-directed variants, eight of them were combined in a mutant Mut8 with both improved enzyme activity and thermostability. The enzyme activity of Mut8 was 3.2-fold higher than wild type, with an increased optimum reaction temperature from 35 ℃ to 40 ℃. The activity of this mutant remained over 93% when incubated at 35 ℃ for 2 h, which was 2.42 times higher than that of wild type. Meanwhile, when the enzymes were incubated at 40 ℃，where the wild type was completely inactivated after 1 h, the residual activity of Mut8 retained 59.0% after 2 h. This study would provide a novel glycosyltransferase with great potential for the industrial production of rebaudioside D and other else steviol glycosides.